Short and long term health effects of parental tobacco smoking during pregnancy and lactation: a descriptive review. Issue 1 (December 2015) - Banderali, G.; Martelli, A.; Landi, M.; Moretti, F.; Betti, F.; Radaelli, G.; Lassandro, C.; Verduci, E.
Abstract A great deal of attention has been focused on adverse effects of tobacco smoking on conception, pregnancy, fetal, and child health. The aim of this paper is to discuss the current evidence regarding short and long-term health effects on child health of parental smoking during pregnancy and lactation and the potential underlying mechanisms. Studies were searched on MEDLINE® and Cochrane database inserting, individually and using the Boolean ANDs and ORs, 'pregnancy', 'human lactation', 'fetal growth', 'metabolic outcomes', 'obesity', 'cardiovascular outcomes', 'blood pressure', 'brain development', 'respiratory outcomes', 'maternal or paternal or parental tobacco smoking', 'nicotine'. Publications coming from the reference list of studies were also considered from MEDLINE. All sources were retrieved between 2015-01-03 and 2015-31-05. There is overall consistency in literature about negative effects of fetal and postnatal exposure to parental tobacco smoking on several outcomes: preterm birth, fetal growth restriction, low birth weight, sudden infant death syndrome, neurodevelopmental and behavioral problems, obesity, hypertension, type 2 diabetes, impaired lung function, asthma and wheezing. While maternal smoking during pregnancy plays a major role on adverse postnatal outcomes, it may also cumulate negatively with smoking during lactation and with second-hand smoking exposure. Although this review was not strictly designed as a systematic review and the PRISMA Statement was not fully applied it may benefit the reader with a promptly and friendly readable update of the matter. This review strengthens the need to plan population health policies aimed to implement educational programs to hopefully minimize tobacco smoke exposure during pregnancy and lactation.